Confucian thought in Cao Cao , Cao Pi, Cao Zhi’s literary works - Aw, Wai Kuan (2017)
Cao Cao, Cao Pi and Cao Zhi were called as “Cao Cao and his sons”. Cao Cao and Cao Pi were the famous politicians and they were also well-known in the literary field. They gathered the scholars from all over the world to form a group to develop their literary writing effectively and enhanced the social status of the refined scholars. Cao Cao and his sons were known as the outstanding representatives in the literary field during that time. This paper is to analyze the Confucianism thoughts of Cao Cao and his sons and summarize their distinctive ideas such as the relationship between Cao Cao and his sons and “Literary” tradition. There are five chapters in this paper. The first chapter is an introduction which explains the research motivation on Cao Cao and his sons and this is followed by literature review of Cao Cao and his sons. The Late Han Dynasty and Cao Wei Dynasty with Confucianism thoughts are discussed in the second chapter of this paper. This chapter discusses specifically on the changes of Confucianism thoughts in the Late Han Dynasty and Cao Wei Dynasty. It also discusses about the Confucian factor on the Cao Cao and his sons such as diversity thought of “Cao Cao and his sons”. In addition, Cao Cao respected rules which are the rule of law,“Punishment for the first to overcome the political chaos” and the rule of Li“National stability with Li for the first” are both discussed in this chapter. The third chapter of this thesis is about " Literary " tradition, mainly discusses " Literary " expression of emotions and reflection of reality between “Cao Cao and his sons”. Cao Cao and his sons’ "Literary" traditional work mainly refers to "Literary" verse and poetry, while their writing techniques were also similar with "Literary" traditional characteristics. The fourth chapter discusses the impact of "Political Pursuits" in the poetry of“ Cao Cao and his sons”. Cao Cao and Cao Pi focused on material interests of "Political Pursuits ", rather than the spiritual level. However, Cao Zhi explored the cultivation of "Political Pursuits" from the spiritual level. Finally is the conclusion which it summarizes the main points of this paper that is Cao Cao and his sons’ Confucianism thoughts.